Assessment of Serum Angiotensin Converting Enzyme 2 and Urine Albumin to Creatinine Ratio as Early Detection of Diabetic Nephropathy - Jabar, Sarah sattar; Mahammed , Sanad Baqir (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Diabetic nephropathy (DN) is a chronic disease manifested by a decreased glomerular filtration rate (GFR) that leads to the progression of kidney failure and increased incidence of mortality and cardiovascular complications. Type 2 diabetes mellitus (T2DM) is a metabolic disorder that affects multiple organs, including the pancreas, as well as the kidneys, liver, brain, and eyes. Angiotensin-converting enzyme 2 (ACE2) is a component of the renin-angiotensin system, which is highly expressed in renal tubular epithelial cells. This study aims to measure ACE2 and the urine albumin-to-creatinine ratio (ACR) as early detection markers for DN among T2DM patients. The sample size consisted of 135 individuals, who were divided into three groups based on ACR criteria: macroalbuminuria, microalbuminuria, and normoalbuminuria, with healthy subjects serving as the control group. They were intended for Telafer Hospital in Mosul City. The data showed significant differences between patient groups and the control group for glycemic, lipid profile, and kidney function tests. Also, the results showed a considerable association between serum glycemic levels, lipid profiles, kidney function tests, and ACE2 and DN in T2DM patients. From the current data, it can be concluded that ACR and ACE2 play a key protective role in preventing progressive renal damage, which is a good indicator for the early detection of DN.